2020
DOI: 10.1111/petr.13698
|View full text |Cite
|
Sign up to set email alerts
|

Permanent pacemaker implantation in pediatric heart transplant recipients: A systematic review and evidence quality assessment

Abstract: Bradyarrhythmias are a common complication following pediatric OHT and may require permanent pacemaker implantation (PPM). The purpose of this study was to investigate the incidence, predictors, and outcomes of children undergoing PPM implantation following OHT. A PRISMA‐compliant systematic literature review was performed using the PubMed database and the Cochrane Library (end‐of‐search date: January 27, 2019). The Newcastle‐Ottawa scale and the Joanna Briggs Institute tool were used to assess the quality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…The incidence of PM implantation after HT in literature varies between 2% and 24%. [1][2][3][4][5][7][8][9]19,20 Our incidence of 14% is in accordance with this. This variation can be explained by several factors such as difference in follow-up duration, inclusion of paediatric patients, average donor age, and local policy on PM indications.…”
Section: Incidence Of Permanent Pacemakerssupporting
confidence: 85%
See 2 more Smart Citations
“…The incidence of PM implantation after HT in literature varies between 2% and 24%. [1][2][3][4][5][7][8][9]19,20 Our incidence of 14% is in accordance with this. This variation can be explained by several factors such as difference in follow-up duration, inclusion of paediatric patients, average donor age, and local policy on PM indications.…”
Section: Incidence Of Permanent Pacemakerssupporting
confidence: 85%
“…Due to the fact that children are more often affected by cardiomyopathies and congenital cardiac abnormalities and not so much by ischaemic cardiomyopathy, the need for amiodarone use in these recipients is less before HT. 19 Ischaemic time during transplantation was another predictor for early PM implantation. Recently, other studies have found no relationship between ischaemic time and PM implantation, [1][2][3]5,7,9 while it has been suggested as a potential risk factor.…”
Section: Risk Factors Of Permanent Pacemakersmentioning
confidence: 98%
See 1 more Smart Citation
“…Those who develop bradyarrhythmia may need temporary pacing, if they do not have an adequate chronotropic response to isoproterenol in the immediate postoperative period, or permanent pacemaker implantation, if persistent. In a meta-analysis of 7,198 pediatric heart transplant recipients, Mylonas et al [ 17 ] reported a prevalence of 1.9% (137) of that requiring permanent pacemaker implantation. Sinus node dysfunction and complete atrioventricular block were the main indications, more frequently in patients operated using the Lower-Shumway technique.…”
Section: Discussionmentioning
confidence: 99%
“…We are aware that TVR can be caused through injury during myocardial biopsy with the bioptome passing across the tricuspid valve ring. 34,37 Therefore, it can be induced over time due to a higher frequency of endomyocardial biopsies in the context of the post-transplant monitoring. In our centre, the use of rejection monitoring with biopsy has decreased in recent years.…”
Section: Tricuspid Valve Regurgitationmentioning
confidence: 99%